Late-stage diversification of bacterial natural products through biocatalysis - Lazic, Jelena; Filipovic, Vuk; Pantelic, Lena; Milovanovic, Jelena; Vojnovic, Sandra; Nikodinovic-Runic, Jasmina (Frontiers in Bioengineering and Biotechnology, 2024)
Bacterial natural products (BNPs) have been and still are very important sources of leads for drug development and chemical novelty. The possibility to perform late-stage diversification of these biomolecules is an attractive approach to obtain novel structures by means other than total chemical synthesis or metal complexation reactions. Although biocatalysis is gaining popularity within the context of green chemistry, a vast majority of the sequenced genome data aimed at deciphering metabolic pathways for BNP biosynthesis, possibly containing additional tailoring enzymes, remains underexplored. In this review, we report a systematic overview of biotransformations of 21 molecules, which include derivatization by halogenation, esterification, reduction, oxidation, alkylation and nitration reactions, as well as degradation products as their sub-derivatives. These BNPs were grouped based on their biological activities into antibacterial (5), antifungal (5), anticancer (5), immunosuppressive (2) and quorum sensing modulating (4) compounds. This study summarized 73 derivatives and 16 degradation sub-derivatives originating from 12 BNPs. The remaining 9 BNPs have not been reported as substrates in biotransformation reactions. The highest number of 28 biocatalytic reactions was reported for the antibacterial drug vancomycin, followed by 18 reactions reported for the immunosuppressive drug rapamycin, suggesting that research focus to date was more on BNPs that were already in clinical use. The most common biocatalysts include oxidoreductases, transferases, lipases, isomerases and haloperoxidases. This review highlights biocatalytic routes for the late-stage diversification reactions of BNPs, which potentially help to recognize the structural optimizations of bioactive scaffolds for the generation of new biomolecules, eventually leading to drug development.